Terra Rossa in the Mediterranean Region: Parent Materials, Composition and Origin - Goran Durn (Geologia Croatica, 2003)
In the past, the term “terra rossa” became quite a common indication for all limestone derived red soils in the Mediterranean region. Today, in some classification systems based on the Mediterranean climate as the major soil differentiating criterion, the term terra rossa is used as a name for the soil subclass “Modal Fersiallitic Red soil” when situated on limestones (DUCHAUFOUR, 1982). However, several national soil classifications (e.g. Croatian, Italian, Israeli) retained the term “terra rossa” for the hard limestone derived red soils. The nature and relationship of terra rossa to underlying carbonates is a long-standing problem which has resulted in different opinions with respect to the parent material and origin of terra rossa. Terra rossa is a reddish clayey to silty-clay material, which covers limestone and dolomite in the form of a discontinuous layer ranging in thickness from a few centimetres to several metres. It is also found along cracks and between bedding surfaces of limestones and dolomites. Thick accumulations of terra rossa like material are situated in karst depressions in the form of pedo-sedimentary complexes. A bright red colour is a diagnostic feature of terra rossa and is a result of the preferential formation of haematite over goethite, i.e. rubification. Terra rossa can be considered as soil, vetusol, relict soil (non-buried-paleosol), paleosol or pedo-sedimentary complex (soil-sediments) among different authors. Most authors today believe that terra rossa is polygenetic relict soil formed during the Tertiary and/or hot and humid periods of the Quaternary. However, some recent investigation in the Atlantic coastal region of Morocco (BRONGER & SEDOV, 2002) show that at least some terra rossa previously referred to as polygenetic relict soils should be regarded as Vetusols. In some isolated karst terrain, terra rossa may have formed exclusively from the insoluble residue of limestone and dolomite but much more often it comprises a span of parent materials including, for example, aaeolian dust, volcanic material or sedimentary clastic rocks which were derived on carbonate terrain via different transport mechanisms. BOERO & SCHWERTMANN (1989) concluded that it is of little relevance for the process of rubification whether the primary Fe sources are autochthonous or allochthonous as long as the general pedoenvironment remains essentially suitable for the formation of terra rossa. This pedoenvironment is characterised by an association of Mediterranean climate, high internal drainage due to the karstic nature of a hard limestone and neutral pH conditions. Terra rossa is formed as a result of: (1) decalcification, (2) rubification and (3) bisiallitization and/or monosiallitization. Since Fed/clay ratios are relatively uniform in most terra rossa, translocation of clay particles is responsible for the distribution of the red colour throughout the whole profile. However, since terra rossa soils have been exposed to various climatic fluctuations they can be affected by eluviation, yellowing and secondary hydromorphy. Erosion and deposition processes which were superimposed on karst terrains and induced by climatic changes, tectonic movements and/or deforestation might be responsible for both the patchy distribution of terra rossa and thick colluvial or alluvial terra rossa accumulations in uvala and dolina type of karst depressions (pedo-sedimentary complexes, soil-sediments).